Influence of the informal primary caretaker on glycemic control among prepubertal pediatric patients with type 1 diabetes mellitus - Jessie Nallely Zurita-Cruz; Elisa Nishimura-Meguro; Miguel Angel Villasís-Keever; Maria Elena Hernández-Méndez; Eulalia Garrido-Magaña; Aleida De Jesús Rivera-Hernández
Abstract Objectives: In prepubertal type 1 diabetic patients (DM1), the availability of an informal primary caregiver (ICP) is critical to making management decisions; in this study, the ICP-related risk factors associated with glycemic control were identified. Patients, materials, and methods: A comparative cross-sectional study was performed. Fifty-five patients with DM1 under the age of 11 years were included. The patient-related factors associated with glycemic control evaluated were physical activity, DM1 time of evolution, and adherence to medical indications. The ICP-related factors evaluated were education, employment aspects, depressive traits (Beck questionnaire), family functionality (family APGAR), support of another person in patient care, stress (Perceived Stress Scale), and socioeconomic status (Bronfman questionnaire). Multivariate logistic and linear regression analyses were performed. Results: The patients' median age was 8 years; 29 patients had good glycemic control, and 26 were uncontrolled. The main risk factor associated with glycemic dyscontrol was stress in the ICP (OR 24.8; 95% CI 4.06-151.9, p = 0.001). While, according to the linear regression analysis it was found that lower level of education (β 0.991, 95% CI 0.238-1.743, p = 0.011) and stress (β 1.918, 95% CI 1.10-2.736, p = 0.001) in the ICP, as well as family dysfunction (β 1.256, 95% CI 0.336-2.177, p = 0.008) were associated with higher levels of glycated hemoglobin. Conclusions: Level of education and stress in the ICP, as well as family dysfunction, are factors that influence the lack of controlled blood glucose levels among prepubertal DM1 patients.